2019
DOI: 10.1002/joa3.12252
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic preconditioning and its role in the prevention of new onset atrial fibrillation post‐cardiac surgery. A meta‐analysis of randomized control trials

Abstract: Background The denouement of remote ischemic preconditioning on new onset atrial fibrillation (NOAF) post‐cardiac surgery is not well‐established. An updated meta‐analysis of randomized control trials was performed by comparing remote ischemic preconditioning with controls and the outcome of interest was NOAF. Methods The systemic review was performed in accordance with the PRISMA (Preferred reporting items for systemic review) and AHA (American Heart Association) guidelines. PubMed database was searched to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In this study, we synthesized the current evidence from RCTs and showed that RIPC is effective for preventing AKI after cardiac surgery. Besides the potential preventative efficacy on AKI, previous studies have shown that RIPC is also effective to attenuate perioperative myocardial injury ( 43 ) and reduce the risk of new onset atrial fibrillation ( 44 ) in patients undergoing cardiac surgery and may reduce mortality in patients receiving volatile inhalational agent anesthesia ( 34 ). Taken together, these findings support the benefits of RIPC use for patients undergoing cardiac surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we synthesized the current evidence from RCTs and showed that RIPC is effective for preventing AKI after cardiac surgery. Besides the potential preventative efficacy on AKI, previous studies have shown that RIPC is also effective to attenuate perioperative myocardial injury ( 43 ) and reduce the risk of new onset atrial fibrillation ( 44 ) in patients undergoing cardiac surgery and may reduce mortality in patients receiving volatile inhalational agent anesthesia ( 34 ). Taken together, these findings support the benefits of RIPC use for patients undergoing cardiac surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…We did not have access to detailed information regarding potential medical treatment (anticoagulation and/or rate control), since these data are not registered in the Danish National Patient Registry. A recent meta‐analysis did not find any effect of RIPC on the risk of postoperative atrial fibrillation [26]. However, future clinical trials should register this potential adverse effect of RIPC in relation to non‐cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using pigs and rats showed that a vago-splenic axis was involved in the cardioprotection of RIPC [25]. Substances such as adenosine [26], bradykinin, opioids [27], microvesicles [28], microRNA-144 [29], nitric oxide [30,31], interleukin (IL)-10 [32] and stromal cell-derived atrial fibrillation post-cardiac surgery seems to be more confirmative [14]. In the meantime, there is also a growing interest in understanding non-anesthetic effects of narcotics [15].…”
Section: Myocardial Ischemia and Reperfusion Injurymentioning
confidence: 99%